2012
DOI: 10.5539/esr.v2n1p33
|View full text |Cite
|
Sign up to set email alerts
|

On the Ultra-Low-Frequency Magnetic Field Depression for Three Huge Oceanic Earthquakes in Japan and in the Kurile Islands

Abstract: The depression (reduction in amplitude) of ULF (ultra-low-frequency) magnetic field variations observed on the Earth's surface is found for the recent huge Japan earthquake (EQ) (magnitude (M) ~ 9.0) on March 11, 2011 which is a typical oceanic EQ of the plate type. In order to confirm the presence of such a ULF depression, we have also studied the additional two huge oceanic EQs in the Kurile islands (M@8), and similar ULF depressions have also been detected. This suggests that such a ULF depression seems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Even with using the same ULF data, we can study a rather new topic of depression of ULF horizontal magnetic field initially discovered by Molchanov et al (2014) [75][76][77][78][79], which is the depletion in the intensity of nighttime irregular pulsations from the magnetosphere. This effect is not so popular even in the academic society, but it is suggested by them that this effect is attributed to the lower ionospheric turbulences [76,77] just like the subionospheric VLF/LF perturbation [16,30].…”
Section: Ulf Magnetic Field Depressionmentioning
confidence: 94%
“…Even with using the same ULF data, we can study a rather new topic of depression of ULF horizontal magnetic field initially discovered by Molchanov et al (2014) [75][76][77][78][79], which is the depletion in the intensity of nighttime irregular pulsations from the magnetosphere. This effect is not so popular even in the academic society, but it is suggested by them that this effect is attributed to the lower ionospheric turbulences [76,77] just like the subionospheric VLF/LF perturbation [16,30].…”
Section: Ulf Magnetic Field Depressionmentioning
confidence: 94%
“…The spatial scale of ionospheric perturbations for the 2011 Japan Earthquake was considerably smaller, as compared with that for the 2004 Sumatra Earthquake. In addition, Hayakawa et al (2013) found a large depression of ULF (ultra-low-frequency) magnetic field variations observed on the Earth's surface on March 6. They also studied two other huge oceanic earthquakes in the Kurile Islands and found similar ULF depressions.…”
Section: M90 Tohoku-oki Earthquakementioning
confidence: 95%
“…Open Journal of Earthquake Research in Kyushu). The definition of this relative depression is given in [123] [124]. The top panel indicates the temporal evolutions of Dst and the occurrence of EQs with M greater than 5.…”
Section: Further Examplesmentioning
confidence: 99%